Efficiency of Educational Games on Mathematics Learning of Students at Second Grade of Primary School - Chizary, Forouzan; Farhangi, Abdolhassan (Journal of History Culture and Art Research, 2017)
Nowadays, children learn a lot from games, in other word these games have a constructive and educative aspect. There has been a progress in science and technology and this progress changes the people’s way of living. This development and progress also change the teaching and learning method. According to these changes, a new generation of educational tools has been designed to help the student to learn in a modern method. In general, the games are used as effective educational tools for enhancing the learning and comprehension of complex issues. The purpose of this research is the efficiency of educational games on mathematics learning of second elementary students of Tehran. This study adapted descriptive-survey method and collect data by questionnaire. Statistical population of this study is the female second student of Tehran elementary schools. 30 students have been selected as sample. These 30 students were divided into two groups of 15, one group is experiment group and the other is the control group. SPSS software was used to analyze data. Results showed that the educational games influence the motivation and mathematics learning of female second elementary students and enhance their intelligence quotient (IQ).